KEKERABATAN Bulbophyllum dan Vanda DI PEKANBARU BERDASARKAN KARAKTER MORFOLOGI - Fitriani K. U; Herman '; Nery Sofiyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Bulbophyllum and Vanda are tropical orchids that are widely distributed in many regions inIndonesia, as well as in Pekanbaru, Riau. These genera have their own beauty with uniquemorphological characters, therefore they attract most people especially orchid lover. Thisresearch aimed to identify the species of Bulbophyllum and Vanda in Pekanbaru and todetermine their relationship based on their morphological characters. One hundred eighteencharacters were scored from 10 orchid species, these characters were then analyzed usingNTSyst 2.02. The result identified five Bulbophyllum species (B. vaginatum, B. medusa,B.machrantum, B. echinolambium and B. coroliferum) and five Vanda species (V. teres, V.dearei, V. limbata, V. tricolorand V. sumatrana). The similarity coefficient was rangedfrom 0.24-0.72. The dendogram was mainly divided into two groups (A and B). Group Aconsisted of all Vanda species while B consisted of all Bulbophyllum species.